Quantification of Slackia and Eggerthella spp. in Human Feces and Adhesion of Representatives Strains to Caco-2 Cells - Cho, Gyu-Sung; Ritzmann, Felix; Eckstein, Marie; Huch, Melanie; Briviba, Karlis; Behsnilian, Diana; Neve, Horst; Franz, Charles M. A. P. (Frontiers in Microbiology, 2016)
Eggerthella and Slackia spp. are gut associated bacteria that have been suggested to play roles in host lipid and xenobiotic metabolism. A quantitative PCR method for the selective enumeration of bacteria belonging to either the genus Eggerthella or Slackia was developed in order to establish the numbers of these bacteria occurring in human feces. The primers developed for selective amplification of these genera were tested first in conventional PCR to test for their specificity. Representative species of Eggerthella and Slackia, as well as closely related genera of the Coriobacteriia, were included in the investigation. The selected primers were shown to be capable of specific amplification of species of the genera Eggerthella and Slackia, but not all species of the genera may be amplified by the respective primers. Their use in qPCR experiments to assess the levels of S. equolifaciens and E. lenta in the feces of 19 human volunteers showed they occurred at mean counts of 7 x 105 and 3.1 x 105 CFU/g for Eggerthella spp. and Slackia spp., respectively. Electron microscopy investigations showed that while E. lenta cells exhibited slender and very regular shaped rods, Slackia cells showed a remarkably pleomorphic phenotype. Both species did not appear to have fimbrae or pili. Some S. equolifaciens cells showed a characteristic “ribbon” of presumably extracellular material around the cells, particularly at the areas of cell division. The two species also differed markedly in their adhesion behavior to Caco-2 cells in cell culture, as E. lenta DSMZ 15644 showed a high adhesion capacity of 74.2% adherence of the bacterial cells added to Caco-2 cells, while S. equolifaciens DSM 24851T on the other hand showed only low adhesion capability, as 6.1% of bacterial cells remained bound. Speculatively, this may imply that the ecological compartments where these bacteria reside in the gut may be different, i.e. E. lenta may be associated more with the gut wall, while Slackia may be free living in the lumen.